Feather barbs as a good source of mtDNA for bird species identification in forensic wildlife investigations - Speller, Camilla F (BioMed Central, 2011)
BACKGROUND: The ability to accurately identify bird species is crucial for wildlife law enforcement and bird-strike investigations. However, such identifications may be challenging when only partial or damaged feathers are available for analysis. RESULTS: By applying vigorous contamination controls and sensitive PCR amplification protocols, we found that it was feasible to obtain accurate mitochondrial (mt)DNA-based species identification with as few as two feather barbs. This minimally destructive DNA approach was successfully used and tested on a variety of bird species, including North American wild turkey (Meleagris gallopavo), Canada goose (Branta canadensis), blue heron (Ardea herodias) and pygmy owl (Glaucidium californicum). The mtDNA was successfully obtained from 'fresh' feathers, historic museum specimens and archaeological samples, demonstrating the sensitivity and versatility of this technique. CONCLUSIONS: By applying appropriate contamination controls, sufficient quantities of mtDNA can be reliably recovered and analyzed from feather barbs. This previously overlooked substrate provides new opportunities for accurate DNA species identification when minimal feather samples are available for forensic analysis.